Makna Simbolisasi Ayam Dalam Upacara Agama Dan Keagamaan Masyarakat Hindu Di Kabupaten Gianyar Bali - I Nyoman Warta (Kamaya: Jurnal Ilmu Agama, 2019)
This research is a merger of library research (library research) with a philosophical view on the field. The material objects are chicken symbols in every religious and religious ceremony in Hindu society in Bali, while the formal object is the philosophy of religion. The combination of this research is to provide a new understanding of the conception of Hindu societies in Bali about the meaning of symbols and their importance to the life of mankind.This research was conducted to answer problems related to the use of symbols in the traditions of religious rituals and religious traditions of the Hindu community. In more detail, this research is to answer questions about what the symbolic meaning of chickens in the religious and religious life of the Hindu community in Bali and how the influence of the use of symbolic chicken in the religious life of the Hindu community. Disclosure of the meaning contained in the symbolization of the chicken is to show the strength of the relationship between religion and culture in every tradition in Hindu society. The meaning contained in the symbolization of chicken shows three levels of human symbols, namely ethical, aesthetic and religious levels. Symbolization of chickens shows a tendency towards harmonizing human relations both horizontally (social harmonization) and transcendental vertical (relationship with God Almighty). In expressing the meaning in each chicken use in religious and religious ceremonies, it is used as an approach, such as a description to reveal what it is about symbolizing chickens. Interpretation and hermeneutics to provide an interpretation of the meaning in the use of chicken symbolization and heuristics used to form a comprehensive view of life in Hindu society.